Listeria monocytogenes in a brazilian pork production chain and adhesion features of isolates - Silva, Danilo Augusto Lopes da (2019)
L. monocytogenes is present at low frequencies in animals to be slaughtered but may persist for long periods in the food processing environment. In the present study, L. monocytogenes contamination was evaluated at different stages of a pork meat production chain in the state of Minas Gerais. Ten lots of pigs were sampled at different stages of the production chain, covering samples from termination sheds, slaughtering (after bleeding, after singeing, after evisceration and after final washing), processing (knives, deboning tables and hand handlers) and end products (ribs, shoulder, ham and sausage) totaling 670 samples. All samples were submitted to L. monocytogenes detection, and the isolates obtained were characterized by biochemical analyzes, serogroups, virulence genes, PFGE, antibiotic susceptibility and adhesion ability. The results revealed the low occurrence of Listeria spp. in the pork production chain evaluated. However, four sausage samples tested (40%) were positive for Listeria spp., with L. monocytogenes identified in two (20%). Ten isolates were identified as L. monocytogenes (eight from serogrounp 1/2a or 3a and two from serogrounp 4b, 4d or 4e), all positive for virulence-related genes hlyA, iap, plcA, actA, inlA, inlB, inlC and inlJ and susceptible to the tested antibiotics. A sausage sample was contaminated by both serogroups 1/2a or 3a and 4b, 4d or 4e. Isolates from serogroup 1/2a or 3a obtained at visits 5 and 6 showed distinct genetic profiles by PFGE, suggesting that contamination may come from a different source. The adhesion potential exhibited by Listeria spp. isolates (n = 18) ranged from weak (serogroup 4b, 4d or 4e) to moderate (L. innocua and L. monocytogenes serogroup 1/2a or 3a). Despite the low occurrence of L. monocytogenes, pathogenic serogroups were detected in sausage, requiring industry control measures. Since L. monocytogenes is a pathogen capable of adhering to various surfaces and forming biofilms, which may explain its persistence in food processing environments, this work also evaluated L. monocytogenes adhesion capacity and the interference of stress factors on adhesion capacity of selected strains (L. monocytogenes strains belonging to lineages I and II, also coming from the meat processing environment, characterized in parallel work by strong adhesion potential (one isolate) and persistence capacity in the processing environment for 3 years (two isolates)), were incorporated into this work and tested with 3 selected isolates from sausage samples. These isolates were submitted to adhesion potential and minimum inhibitory concentration tests against four disinfectants. The adhesion capacity of the selected isolates was also tested considering: disinfectant dilutions, NaCl concentrations and curing salts, incubation time and temperature. Each isolate was classified according to its adherence capacity as weak, moderate or strong. The four disinfectants tested were effective in eliminating L. monocytogenes. The isolates selected for stress tests showed greater adhesion capacity at 37 °C/72 hours, and the BHI broth with 5% NaCl and quaternary ammonia (1: 1,024) were ineffective in inhibiting polystyrene adhesion. The collected data allowed the identification of the adhesion potential of L. monocytogenes, the efficacy of the sanitizers tested in the control of contamination by this pathogen and the adhesion capacity in the presence of quaternary ammonium (1: 1,024) and salts of some isolates. Considering their ability to adhere to stressful conditions in the tests described above and the fact that they have the genome sequenced by (cg) MLST in parallel studies four isolates of L. monocytogenes belonging to strains I and II from the meat processing environment were further investigated for stainless steel biofilm formation capacity in the presence of curing salt 7.5% (lineage I) and quaternary ammonium (1: 1,024) (lineage II). Additionally, a predictive analysis of gene expression related to biofilm formation and adaptation to stressful conditions was performed by qPCR assays (previously detected by in silico genome analysis of selected isolates, characterized by (cg) MLST in parallel work). L. monocytogenes biofilm formation in stainless steel was tested in two different systems (microplate and coupons) at 37 °C for 72 hours. Assays were performed as biological triplicates and included appropriate controls to verify significant differences by analysis of variance (p < 0.05). It was observed that the tested strains (I and II) were able to form stainless steel biofilm. Although the treatments used in each strain were significant in reducing the biofilm formation (p < 0.05), the isolates were able to form biofilm under the stress condition evaluated. L. monocytogenes biofilm suspensions from stainless steel coupon testing gave positive results in qPCR assays for eleven target genes tested. In general this work showed that the pig did not appear to be a representative carrier of this pathogen. Even though it was not possible to obtain positive samples for L. monocytogenes from the slaughtered and processing environment, obtaining final products (sausage) contaminated with pathogenic serogroups shows the health risk to the final consumer and the ability of this pathogen to persist in the pork meat processing environment once its presence has been detected in the final product. The isolates of L. mococytogenes obtained belong to phylogenetic lineages recognized for being highly adapted to the food processing environment, and showed ability to adhere to the tested surfaces under stress conditions. The recognized ability of this pathogen to form biofilm on surfaces commonly found in the meat processing environment could also be demonstrated, the tested isolates were able to form stainless steel biofilm in the presence of agents usually used for sausage preparations and also in the processing plant cleaning / disinfection procedures. The in silico analysis of cg MLST allowed the identification of genomic regions related to biofilm formation and adaptation to stressful environmental conditions in lineages I and II isolates. It is also possible to detect the action of this genetic machinery in the stainless steel biofilm formation under action of stress factors, by predicting the expression of eleven target genes performed by qPCR.